Analysis of the Implementation of Sharia Principles in BSI Hasanah Card Products in Increasing Customer Loyalty of Bank Syariah Indonesia (Case Study of BSI KC Adam Malik, Bengkulu City) - Aditia Ningrum Syahfitri (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study aims to analyze the implementation of sharia principles in BSI Hasanah Card products and to examine its relationship with increasing customer loyalty at Bank Syariah Indonesia (BSI) Adam Malik Branch, Bengkulu City. The study employed a descriptive qualitative approach, collecting data through in-depth interviews, participatory observation, and documentation involving the Branch Manager, Customer Service staff, and BSI Hasanah Card holders. Data analysis was conducted using the Miles and Huberman model through three stages: data reduction, data display, and conclusion drawing. The findings reveal that BSI Hasanah Card has consistently implemented sharia principles across four main dimensions: (1) the anti-riba principle, realized through the elimination of the interest system and its replacement with a service fee (ujrah); (2) the anti-maisir principle, enforced by restricting transactions only to BSI-verified merchants; (3) the anti-gharar principle, ensured through information transparency and contractual clarity before customers use the product; and (4) the justice principle, reflected in a mutual agreement mechanism where both parties fully understand their rights and obligations. The Hasanah Card employs three primary contracts in accordance with DSN-MUI Fatwa No. 54/DSN-MUI/X/2006, namely Kafalah, Qardh, and Ijarah. A positive relationship was found between the implementation of sharia principles and customer loyalty, evidenced by three loyalty indicators: continuous product usage, resistance to competitor offerings, and willingness to recommend the product to others.